Influence of motivation on academic performance: an analysis of motivational assessment in mathematics learning - Martínez-Ariza, Ligia; Cudris-Torres, Lorena; Echeverría-King, Luisa Fernanda; Niño-Vega, Jorge Armando (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of the study consisted of relating motivation with academic performance in mathematics in schoolchildren in northern Colombia, through the use of Pearson's correlation coefficient, applying the motivational assessment of the learning process (EMPA) questionnaire, to establish the levels of extrinsic and intrinsic motivation of the 65 students belonging to the sample. Academic performance was obtained through second source information provided by the academic coordination of the institution understudy, a quantitative and correlational approach was used. The results show a significant negative correlation in the dimensions of intrinsic and extrinsic motivation with academic performance. Given this, new lines of research are proposed, especially accompaniment by parents and guardians, and socioeconomic characteristics and their relationship to academic motivation.